Udviklingen af kynisme fra politistuderende til betjent - Christian Dyrlund Wåhlin-Jacobsen; Elisabeth Naima Mikkelsen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The literature shows that some police officers develop cynicism early in their careers, i.e., develop a critical or distrusting attitude that is often aimed towards citizens. Despite a recent increase in societal focus on how citizens experience interaction with the police, we have only a limited understanding of how cynicism develops in Scandinavia, including Denmark. In this study, we  present statistical analyses of questionnaire data collected among police employees in three waves between the beginning of their training to become police officers and after four years of active service. The results demonstrate that cynicism should be approached as a multi-faceted phenomenon. This is because participants generally report a decrease in cynicism towards citizens, but an increase in cynicism in connection with other aspects of police work. Post hoc analyses, however, indicate that high  emotional demands, as well as violence and threats may contribute to an increased cynicism towards citizens.